Ethereum Blockchain Network Implementation for IoT Platform - Zainal Abidin, Mohamad Hafizat; Suchaad, Saravid; Mashiko, Koichiro; Ismail, Nordinah (International Journal of Integrated Engineering, 2019)
Internet of things (IoT) is becoming increasingly important and ubiquitous in home and industries. It makes object a part of the Internet and fuses the digital and physical world together. However, if not properly secured, IoT device can be vulnerable to tampering that can change the content of the data stored in the network. Blockchain, a technology used in cryptocurrency, can be used for addressing the security and privacy challenges in IoT. Blockchain can be beneficial to IoT by adding more security layer and reducing dependency on a central authority. This paper proposed to develop a blockchain based platform for IoT application. Blockchain technology can be utilized to provide a decentralized network, creating a more secured IoT system. The proposed blockchain network will be based on Ethereum blockchain network allowing the use smart contract application for management of IoT devices. Experiment is conducted to show the feasibility of the blockchain based platform. The proposed blockchain based platform is capable of managing several IoT devices connected to the network.